2021
DOI: 10.1101/2021.05.05.442784
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 B.1.1.7 and B.1.351 variants of concern induce lethal disease in K18-hACE2 transgenic mice despite convalescent plasma therapy

Abstract: SUMMARYSARS-CoV-2 variants of concern (VoCs) are impacting responses to the COVID-19 pandemic. Here we present a comparison of the SARS-CoV-2 USA-WA1/2020 (WA-1) strain with B.1.1.7 and B.1.351 VoCs and identify significant differences in viral propagation in vitro and pathogenicity in vivo using K18-hACE2 transgenic mice. Passive immunization with plasma from an early pandemic SARS-CoV-2 patient resulted in significant differences in the outcome of VoC-infected mice. WA-1-infected mice were protected by plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 70 publications
4
9
0
1
Order By: Relevance
“…3G ). We have also observed a similar fitness advantage of a natural SARS-CoV-2 SA natural isolate over SARS-CoV-2 WA-1 ( 24 ).…”
Section: Resultssupporting
confidence: 63%
“…3G ). We have also observed a similar fitness advantage of a natural SARS-CoV-2 SA natural isolate over SARS-CoV-2 WA-1 ( 24 ).…”
Section: Resultssupporting
confidence: 63%
“…37 Multiple recent in situ and animal model studies have confirmed that emerging variants indeed cause higher viral load and prolong viral shedding, however, whether these properties are attributed to the mutations linked to RBD:ACE2 binding is still not clear. 37,44,49,50,53,54 Of interest, multiple studies have demonstrated that the WT strain of SARS-CoV-2 had gained instability for RBD:ACE2 binding when it added new muta- of the viral membrane with the host cell. 24,42,50,58 Recent evidence from in situ studies has demonstrated enhanced virus-host membrane fusion for the B.1.617 lineage variants which contain P681R.…”
Section: Increased Transmissibility and Virulencementioning
confidence: 99%
“…It has been suggested that selected nonsynonymous mutations may be associated with more severe disease and inferior outcomes [ 6 ]. In vivo data indicated that infection with VOCs such as B.1.1.7 and B.1.351 reveal significant differences in pathogenicity with increased clinical progression and lower survival [ 7 ]. However, this has not been confirmed in the observational studies of hospitalized patients [ 8 ].…”
Section: Introductionmentioning
confidence: 99%